2020
DOI: 10.1037/spq0000403
|View full text |Cite
|
Sign up to set email alerts
|

Infusing global and intercultural perspectives to transform school psychology and school psychologists.

Abstract: School psychology has been criticized for limited attention to and limited evidence-based resources for diverse populations in domestic and international settings, in part because of its foundations on psychological knowledge generated primarily in North America and Western Europe. Moreover, in the past 25 years, the profession has made insufficient progress in changing its focus toward an ecological systems perspective as initially envisioned by Conoley and Gutkin in 1995 and revisited in this issue. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…To foster knowledge regarding terminology relevant to the delivery of culturally responsive services, Nastasi, Chittooran, Arora, and Song (2020) provided an impressive account of critical constructs associated with embracing a global and intercultural perspective. These authors, who have been leaders in international and cultural school psychology initiatives, explained that building intercultural competence requires engagement at a metacultural level, whereby school psychology professionals continuously reflect on and revise their attitudes and expectations.…”
Section: Understanding and Integrating The Past Present And Futurementioning
confidence: 99%
“…To foster knowledge regarding terminology relevant to the delivery of culturally responsive services, Nastasi, Chittooran, Arora, and Song (2020) provided an impressive account of critical constructs associated with embracing a global and intercultural perspective. These authors, who have been leaders in international and cultural school psychology initiatives, explained that building intercultural competence requires engagement at a metacultural level, whereby school psychology professionals continuously reflect on and revise their attitudes and expectations.…”
Section: Understanding and Integrating The Past Present And Futurementioning
confidence: 99%
“…As has been widely debated, transformation has been advocated since the birth of school psychology with recent world and societal events adding to the urgency of change (Nastasi et al, 2020). From the APA DSP and NASP partnership, Sheridan and D'Amato (2003) summarized what they understood from the field was needed to help solve the many school, child, and family related issues that trouble society and lead to continued educational inequalities.…”
Section: What's So Special About the School Psychology Specialty?mentioning
confidence: 99%
“…School psychologists must become effective change agents and consultants when offering primary, secondary, and tertiary interventions for teachers, parents, and students (Hughes et al, 2020; Nastasi et al, 2020). We envision more system-wide screening for early intervention and the expansion of psychological services for children ages 0 to 3 and their parents.…”
Section: The Future: School Psychology In a Changing Worldmentioning
confidence: 99%
“…The School Psychology Unified Anti-Racism Statement and Call to Action (Garcia Vazquez et al, 2020) identified several steps for the profession of school psychology to actively engage in antiracism. To begin, school psychologists must practice intercultural competence, defined by Nastasi and colleagues (2020) as a process of personal cultural awareness, open engagement with others, and willingness to reconsider assumptions and viewpoints. To genuinely enact equity for students and their families, school psychology scholars and practitioners must engage in continued learning and self-reflection and must commit to making this work a foundational component of our profession.…”
Section: Centering Social Justice and Equity In School Psychologymentioning
confidence: 99%